THE IMPACT OF DIGITAL TRANSFORMATION ON ORGANIZATIONAL EFFICIENCY: A STRATEGIC MANAGEMENT PERSPECTIVE (American Journal of Interdisciplinary Research and Development, 2024)
In the contemporary business landscape, digital transformation has become a crucial element impacting the competitiveness and sustainability of organizations. This article examines the influence of digital transformation on organizational efficiency from a strategic management perspective. By implementing digital tools such as automation, cloud computing, artificial intelligence (AI), and data analytics, companies can streamline operations, enhance decision-making, and optimize performance. The findings indicate that while digital transformation offers substantial benefits, successful implementation requires a strategic alignment with organizational goals, effective change management, and a focus on employee training and development. This paper also explores the strategic challenges organizations face and provides actionable recommendations for overcoming them to achieve optimal efficiency.